2019
DOI: 10.1111/gtc.12719
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid, extracted from Sanguisorba officinalis, induces G1 arrest by modulating PTEN activity in B16F10 melanoma cells

Abstract: In Chinese medicine, herbal medicine is commonly used to treat individuals suffering from many types of diseases. We thus expected that some herbal medicines would contain promising compounds for cancer chemotherapy. Indeed, we found that Sanguisorba officinalis extracts strongly inhibit the growth of B16F10 melanoma cells, and we identified ellagic acid (EA) as the responsible ingredient. B16F10 cells treated with EA exhibited strong G1 arrest accompanied by accumulation of p53, followed by inactivation of AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…It is reported that the water extract of S. officinalis, when used at a relatively low dose (IC 50 < 200 μg/ml) and in combination with 5-fluorouracil, could increase the cytotoxic effect on two colorectal cancer cell lines HCT-116 and RKO by promoting the reactive oxygen species-mediated mitochondrial caspasedependent apoptotic pathway (Liu et al, 2016). A similar effect was observed when ellagic acid isolated from the alcohol extracts of S. officinalis was used in combination with cisplatin treatment (Tan et al, 2019), as reported by numerous scientific studies (García-Niño and Zazueta, 2015;Ceci et al, 2018).…”
Section: Antitumor Effectssupporting
confidence: 74%
See 2 more Smart Citations
“…It is reported that the water extract of S. officinalis, when used at a relatively low dose (IC 50 < 200 μg/ml) and in combination with 5-fluorouracil, could increase the cytotoxic effect on two colorectal cancer cell lines HCT-116 and RKO by promoting the reactive oxygen species-mediated mitochondrial caspasedependent apoptotic pathway (Liu et al, 2016). A similar effect was observed when ellagic acid isolated from the alcohol extracts of S. officinalis was used in combination with cisplatin treatment (Tan et al, 2019), as reported by numerous scientific studies (García-Niño and Zazueta, 2015;Ceci et al, 2018).…”
Section: Antitumor Effectssupporting
confidence: 74%
“…Methanol extracts of S. officinalis (40, 80, or 120 μg/ml) have demonstrated significant cytotoxic activity against human prostate cancer cells via an intrinsic apoptotic pathway ( Choi et al, 2012a ), in addition to inhibiting the proliferation of human breast cancer cell lines MCF-7 and MDA-MB-231 by inducing S-phase arrest and triggering the mitochondrial pathway of apoptosis ( Wang et al, 2012 ), and causing the blockage of the G1 phase in B16F10 melanoma cells ( Tan et al, 2019 ).…”
Section: Pharmacological Effects Exhibited By Genus Sanguisorbamentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used HG to treat rat MCs to establish a DN model in vitro . EA is a type of polyphenol compound, widely used in Chinese herbal medicines, such as sanguisorba officinalis and pomegranate peel ( 27 , 28 ). Numerous studies have demonstrated that EA possesses multiple biological activities in vitro ( 14 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Filipendula [16], Alchemilla [17], Potentilla [18,19], Sanguisorba [20,21], Rubus [22,23], Fragaria [24], Rosa [25].…”
Section: Ellagic Acid-4acetylarabinoside 101129363mentioning
confidence: 99%